2017
DOI: 10.1007/s00441-017-2698-5
|View full text |Cite
|
Sign up to set email alerts
|

Defective Wnt3 expression by testicular Sertoli cells compromise male fertility

Abstract: Testicular Sertoli cells make a niche for the division and differentiation of germ cells. Sertoli cells respond to increased follicle-stimulating hormone (FSH) and testosterone (T) levels at the onset of puberty by producing paracrine factors which affect germ cells and trigger robust onset of spermatogenesis. Such paracrine support to germ cells is absent during infancy, despite Sertoli cells being exposed to high FSH and T within the infant testis. This situation is similar to certain cases of male idiopathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…Luteinising hormone is responsible for initiating testosterone production by the interstitial endocrine cells. Follicle-stimulating hormone and testosterone stimulation of the sustentacular (Sertoli) cells initiates spermatogenesis and spermiation (Basu et al 2017). In the absence of these hormones, normal stimulation of the testes is compromised; gonadal regression and infertility follow (Miller et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Luteinising hormone is responsible for initiating testosterone production by the interstitial endocrine cells. Follicle-stimulating hormone and testosterone stimulation of the sustentacular (Sertoli) cells initiates spermatogenesis and spermiation (Basu et al 2017). In the absence of these hormones, normal stimulation of the testes is compromised; gonadal regression and infertility follow (Miller et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…6,11,42 Augmented hormonal levels trigger the division and differentiation of germ cells, leading to the initiation of spermatogenesis at puberty. 50 Moreover, both FSH and T promote the supportive role of SCs in this process by regulating SC physiology 6,11 and specifically metabolism 6 through stimulating glycolysis by increasing glucose uptake and/or modulating glycolysis-related enzymes. 6,51,52 Our results on the role of Glo1 in protecting cells from apoptosis through the control of MG-derived AGEs levels are in agreement with the existing literature in other cell models, 26e31,53e55 including oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Through expression analysis in the Sertoli cells of three age groups, it was found that lncWNT3-IT and WNT3 had similar expression trends during the differentiation of Sertoli cells; that is, with the process of Sertoli cell differentiation and maturation, both the expression levels significantly improved, suggesting that they may play an important role in the regulation of cell proliferation and differentiation (Basu et al, 2018;Coombs et al, 2010). It is common knowledge that the vast majority of the Sertoli cells cease proliferation at puberty, when the blood-testis barrier is established and spermatogenesis starts.…”
Section: Lncwnt3-it Affects the Expression Of Wnt3mentioning
confidence: 97%
“…WNT3 is a member of this protein family and affects the critical stages of development and differentiation by activating the typical signalling pathway WNT/β-catenin (Weng et al, 2017). In recent years, new studies have found that the expression of WNT3 in adolescent monkeys Sertoli cells (active spermatogenesis) is significantly higher than that in young monkeys (spermatogenesis) (Basu et al, 2018), and studies in mice have indicated the same. The low expression of the Sertoli cells in WNT3 reduces the expression of connexin 43, a linker molecule essential for germ cell development, indicating that WNT3 expression impairs the Sertoli cell-mediated spermatogenesis and affects male fertility (Basu et al, 2018;Kerr, Young, Horvay, Abud, & Loveland, 2014;Lopez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation